Microwave Assisted Organic Synthesis (MAOS) of Small Molecules as Potential HIV-1 Integrase Inhibitors - Ferro, Stefania (Molecules, 2011)
Integrase (IN) represents a clinically validated target for the development of antivirals against human immunodeficiency virus (HIV). In recent years our research group has been engaged in the stucture-function study of this enzyme and in the development of some three-dimensional pharmacophore models which have led to the identification of a large series of potent HIV-1 integrase strand-transfer inhibitors (INSTIs) bearing an indole core. To gain a better understanding of the structure-activity relationships (SARs), herein we report the design and microwave-assisted synthesis of a novel series of 1-H-benzylindole derivatives.